Analisis Penggunaan Alih Kode Dalam Film “Ngeri-Ngeri Sedap” Karya Bene Dion Rajagukguk - Salsa Bila Nopriyanti Daulay; Yusniati Zai; Pasya Amelia; Rivani Afri Yuli; Emasta Evayanti Simanjuntak; Frinawaty Lestarina Barus (Universitas Palangka Raya, 2023)
The purpose of this research is to find out the form of code switching in the film “Horrible horrors” and to find out the factors that cause code switching to occur. The film “Horrible Horrible” consists of one episode with a duration of about 114 minutes. This film was released on June 2, 2022 and aired on Netflix on April 26, 2022. This film has been successfully watched around 2,812,606 times. Researchers collected data with the method of observing and note-taking techniques. Based on the results of the research and the results of the interviews, the researchers found that the factors causing code switching were caused by several things. The use of two languages in communication is not appropriate because the use of two languages will lead to disintegration. After conducting a search and checking of the film “horrifyingly delicious”, it can be concluded that there are 18 coders in the film “terrifyingly delicious”, of which the 18 characters interact with each other using a mixture of language from other languages. Region to Indonesian